Urgensi Manajemen Pembelajaran di Era Globalisasi - Ari Wibowo Sembiring; Okta Elviana Manurung; Lola Amalia Sibarani; Wardah Sahrani Sibarani; Laila Ali Tanjung; Fauzan Azima (Peneliti.net, 2022)
In essence, the success of an educational institution is strongly influenced by the way in which the institution is managed. Indeed, a good educational institution must be managed with good management as well. As time goes by, the way of learning management will also be different. A good way of learning management in the era of globalization is by adjusting the times, such as the current era of globalization. Objectives: To find out more about the urgency of learning management, and to know ways to manage Islamic education in the era of globalization. By using the research library approach method. So the attitude of indifference to Islamic education caused by the negative impact of technological developments, this certainly should not be allowed. Therefore, this article discusses the urgency of learning management in the era of globalization which contains ways to manage education well in the current era of globalization. Management is needed and important in planning an ideal education by following the times, but the existence of learning management should not be lost.